2020
DOI: 10.3389/fcimb.2020.00360
|View full text |Cite
|
Sign up to set email alerts
|

Interactions Between Gut Microbiota, Host, and Herbal Medicines: A Review of New Insights Into the Pathogenesis and Treatment of Type 2 Diabetes

Abstract: Herbal medicines (HMs) are a major subset of complementary and alternative medicine. They have been employed for the efficient clinical management of type 2 diabetes mellitus (T2DM) for centuries. However, the related underlying mechanisms still remain to be elucidated. It has been found out that microbiota is implicated in the pathogenesis and treatment of T2DM. An interplay between gut microbiota and host occurs mainly at the gastrointestinal mucosal barrier. The host movements influence the composition and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 134 publications
1
24
0
Order By: Relevance
“…For example, many TCMs contain polyphenols, but the polyphenols show less than 10% absorption and about 90–95% of the polyphenols accumulate in colon [ 36 ]. Growing evidence demonstrates orally administrated TCM is affected by enzymes of gut microbiota [ 37 , 38 ]. Nitroreductase and azoreductase are two major reductases in gut bacteria.…”
Section: Mechanisms Of Tcm Alleviating Uc Via the Gut Microbiotamentioning
confidence: 99%
See 1 more Smart Citation
“…For example, many TCMs contain polyphenols, but the polyphenols show less than 10% absorption and about 90–95% of the polyphenols accumulate in colon [ 36 ]. Growing evidence demonstrates orally administrated TCM is affected by enzymes of gut microbiota [ 37 , 38 ]. Nitroreductase and azoreductase are two major reductases in gut bacteria.…”
Section: Mechanisms Of Tcm Alleviating Uc Via the Gut Microbiotamentioning
confidence: 99%
“…Multiple studies showed lower relative abundance of SCFA-producing bacteria, for instance, Faecalibacterium , Clostridium clusters IV and XIVb, Roseburia , Odoribacter , and Leuconostocaceae in UC patients [ 56 , 57 ]. TCM has been found to adjust the gut flora structure and metabolic profiles [ 37 , 58 , 59 ]. It is reported that SCFAs exert their effects through activating G-protein-coupled receptors (GPCRs) and inhibiting histone deacetylases (HDACs) [ 60 62 ].…”
Section: Mechanisms Of Tcm Alleviating Uc Via the Gut Microbiotamentioning
confidence: 99%
“…Dysregulation of intestinal mucosal immune system can progressively lead to autoimmune disease and in ammation-driven carcinogenesis [1]. The gut microbiota has been shown to play critical roles in maintaining intestinal mucosal immune system homeostasis [2][3][4]. The intestinal mucosal immune system includes three different mucosal lymphoid structures: the epithelia, Peyer's patches and the lamina propria [5].…”
Section: Introductionmentioning
confidence: 99%
“…Additional and/or alternative agents (sulfonylureas, thiazolidinediones, α-glucosidase inhibitors, dipeptidyl peptidase-4 inhibitors, and sodium-dependent glucose transporter 2) and injectable medications (insulin and glucagon-like peptide-1) may be considered, as the disease progresses [7]. Complementary and alternative medications may include other therapeutic approaches, although the underlying mechanisms remain to be elucidated [8].…”
Section: Introductionmentioning
confidence: 99%
“…Oligosaccharides in the alimentary tract modulate gut microbiota composition [13]. The microbiota is implicated in T2D pathogenesis and treatment [8]. Transglucosidase decreases postprandial blood glucose levels in individuals with IGT and T2D [14,15].…”
Section: Introductionmentioning
confidence: 99%